Issues on Interpreting - Asgari, Roghiyeh (Ciência e Natura, 2015)
Interpreting is an ancient human practice which clearly predates the invention of writing and translation. Interpreting has existed for a long time. Whenever people met other people who had no common language they had to make do with sing language or find someone who speak both languages (Pochhacker, 2004). Interpreting is a form of translation in which a first and final rendition in another language is produced on the basis of a one-time presentation of an utterance in a source language (ibid). This paper is intended to provide some crucial features presented in interpreting; the quality of which directly affect the quality of interpreting.